Involvement of Wiskott-Aldrich Syndrome Protein Family Verprolin- Homologous Protein (WAVE) and Rac1 in the Phagocytosis of Amyloid- β(1 - 42) in Rat Microglia - Yoshihisa Kitamura; Keiichi Shibagaki; Kazuyuki Takata; Daiju Tsuchiya; Takashi Taniguchi; Peter J. Gebicke-Haerter; Hiroaki Miki; Tadaomi Takenawa; Shun Shimohama (Elsevier, 2003)
Alzheimer's disease (AD) is characterized by the accumulation of extracellular amyloid-β (Aβ) fibrils with microglia. Recently, there has been great interest in the microglial phagocytosis of Aβ, because the microglial pathway is considered to be one of the Aβ clearance pathways in the brain parenchyma. However, the mechanism of microglial phagocytosis of Aβ is not fully understood and, thus, was investigated in this study. At one minute after exposure to Aβ(1 - 42) (Aβ42), Aβ immunoreactivity was detected at the cell surface of microglia. After 1 h, marked immunoreactivity was observed in the cytosolic vesicles. At 12 h, delayed phagocytosis of fibrillar Aβ42 was also observed with the formation of a large phagocytic cup. The microglial cell shape rapidly changed to an ameboid form during the process of phagocytosis. Although neither neural Wiskott-Aldrich syndrome protein (N-WASP) nor WASP interacting SH3 protein (WISH) immunoreactivity was co-localized with filamentous actin (F-actin) distribution, both WASP family verprolin-homologous protein (WAVE) and Rac1 immunoreactivity was co-localized with F-actin in the lamellipodia of phogocytic microglia. These results suggest that WAVE and Rac1 participate in the phagocytosis of Aβ42 by microglia.